Nurses' Experiences of Critical Care in the COVID-19 Intensive Care Unit - Alirez Mirjalili; Samaneh Mirzaei; Khadijeh Nasiriani (Universitas Airlangga, 2022)
Background: The intensive care unit is one of the essential and vital departments of hospitals that accommodate patients in critical condition. Intensive care nurses play an important role in the evaluation, treatment, and management of these patients. The outbreak of the COVID-19 (Coronavirus disease ) pandemic, followed by severe respiratory involvement, highlighted the importance of nurses' performance in the intensive care unit. The aim of this study was to explain the nurses' experiences of nursing care in the COVID-19 intensive care unit.Methods: This study was qualitative content analysis. Participants were 12 nurses who were selected based on purposive sampling. Data collected by semi and unstructured interview. Data analysis was performed based on Graneheim and Lundman (2004) at three-phase. Research trustworthiness was confirmed by four criteria of credibility, transferability, dependability, and conformability.Results: In this study, a total of 1311 meaning units were extracted; after condensation and abstraction, 257 codes were obtained, which were extracted into 32 primary subcategories, eight secondary subcategories, and two themes. The first theme was nursing care inhibitors in the COVID-19 (Coronavirus disease) Intensive Care Unit included five categories: